PENGARUH PELATIHAN KERJA DAN DISIPLIN TERHADAP KINERJA PEGAWAI PADA KANTOR INSPEKTORAT KOTA SIBOLGA - Irfandi Syaputra; Kaharuddin Kaharuddin; Rosmita Ambarita (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research aims determine the Effect of Job Training and Discipline on Employee Performance at the Sibolga City Inspectorate Office. The type of research used in this study is a quantitative research method with a descriptive correlation approach. The sample in this study were employees at the Sibolga City Inspectorate Office with a questionnaire distribution of 85 (eighty-five) respondents. The results of the study show that based on the analysis of the determination coefficient obtained, it is 0.651, this means that what happens to the variation of the dependent variable Employee Performance (Variable Y) is 65.1% determined by the independent variables Job Training (Variable X1) and Discipline (Variable X2) simultaneously and the remaining 34.9% is determined by other factors not discussed in this study. From the results of the t-test in the study, it is known that the calculated t value of Job Training is 7.817, greater than the t table of 7.817 (7.817> 1.98932), then the Job Training variable (X1) has an effect on Employee Performance (Y) at the Sibolga City Inspectorate Office, meaning Ho is rejected, Ha is accepted and Discipline is 4.885> t table 1.98932, then the Discipline variable (X2) has an effect on Employee Performance at the Sibolga City Inspectorate Office, meaning Ho is rejected, Ha is accepted. Meanwhile, from the results of the F test, it is known that the calculated F value is 76.553> F table 3.11 and the significance is 0.000 <0.05 so that the hypothesis stating that Job Training and Discipline have a significant effect together or simultaneously on Employee Performance at the Sibolga City Inspectorate Office can be accepted.